COMBINATION THERAPY OF HIGH-RISK PATIENTS IN REAL CLINICAL PRACTICE. RESULTS OF SYNERGY STUDY. PART 1. ANTIHYPERTENSIVE BRANCH - O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the efficacy and safety of the use of combined antihypertensive therapy with perindopril (as monotherapy or as a fixed combination with amlodipine or indapamide) together with lipid-lowering therapy with rosuvastatin, and to assess the level of satisfaction of doctors with the efficacy and safety of these combinations. Material and methods. 24 008 patients with arterial hypertension (HT) and dyslipidemia were included into the multicentre observational study. Researchers were free to choose a group of drugs and a prescription schedule. Inclusion criteria: age ≥18 years; the confirmed HT; combined therapy, including perindopril (monotherapy or fixed combination with indapamide or amlodipine) and rosuvastatin. The total duration of the study was 8 months (2 visits). At each visit, all patients underwent an office blood pressure (BP) and heart rate (HR) measurement, electrocardiogram registration, and assessment of lipids, electrolytes, creatinine, uric acid blood concentrations, and hepatic transaminase activity. Results. 10 330 men (43%) and 13 678 women (57%) were included into the study. The mean age of the patients was 61.83Ѓ}11.20 years. Ischemic heart disease was found in 9 792 (41%) patients, the history of myocardial infarction – in 12%, the history of stroke – in 6%, atrial fibrillation – in 2 428 (10%), chronic heart failure – in 15 449 (64%), diabetes mellitus – in 6 037 (25%) patients. Previous antihypertensive therapy was not available in 2 504 patients. A significant decrease in systolic and diastolic BP, HR was detected at visit 2 in patients using perindopril containing drugs (monodrug, fixed combinations with indapamide or amlodipine). Target systolic BP levels were achieved in 95% of patients with perindopril monotherapy, in 91% – with a fixed combination of perindjpril/indapamide, and in 88.6% – with perindopril/amlodipine. Doctors noted high satisfaction with the therapy. According to safety assessment the average score for perindopril monotherapy was 9.64, for a fixed combination of perindopril/indapamide – 9.61, for a fixed combination of perindopril/amlodipine – 9.64. Conclusion. Some aspects of the efficacy and safety of antihypertensive therapy in the SYNERGY study are discussed in this article. The use of combination therapy is associated with high efficacy, greater patient adherence to treatment and a lower incidence of discontinuation. All these provisions were confirmed in the SYNERGY study.